1994
DOI: 10.1271/bbb.58.910
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutination Activity ofLactobacillus acidophilusGroup Lactic Acid Bacteria

Abstract: The cells of 28 strains of the Lactobacillus acidophilus group were evaluated for hemagglutination (HA) activity. The activity was found in the surface layer (SL) protein fraction extracted by 2 M guanidine hydrochloride. The most SL proteins from the A group strains (L. acidophilus (A1), L. crispatus (A2), L. amylovorus (A3), and L. gallinarum (A4)) showed HA activity, but the proteins from the B group strains (L. gasseri (B1) and L. johnsonii (B2)) showed no activity. The SL proteins from the A group strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Several LAB are known to adhere to the GI tract through a lectin-like function, by the affinity of a bacterial extracellular molecule and mucus or epithelial cells. 5,[30][31][32] Previously, the influence of proteinase treatment on the adhesion of LAB was investigated, and several strains of LAB were found probably to possess a proteinaceous adhesin(s) on their cell surface. 7) In this study, the adhesion factors of intestinal cells are strongly indicated also to be proteinous molecules in MapA mediating adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Several LAB are known to adhere to the GI tract through a lectin-like function, by the affinity of a bacterial extracellular molecule and mucus or epithelial cells. 5,[30][31][32] Previously, the influence of proteinase treatment on the adhesion of LAB was investigated, and several strains of LAB were found probably to possess a proteinaceous adhesin(s) on their cell surface. 7) In this study, the adhesion factors of intestinal cells are strongly indicated also to be proteinous molecules in MapA mediating adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported that the 1034 lectin (purified) had high HA activity and could recognize a trisaccharide portion (NeuAc:x2-.6GaI/Jl-.4GlcNAc-), common in the (8). and YN266 (C) SLP.…”
Section: Discussionmentioning
confidence: 99%
“…The binding to the Carnoy's-fixed surface mucous layer of human normal colon tissues with B-I034 SLP (whole) and B-I034 lectin (purified) prepared from L. acidophilus JCM I 034 in our previous paper 8 ) was examined by histochemical staining. Figure 2C shows the mucous layer of Carnoy's-fixed human colon seen by the HID (for sulfated mucopolysaccharide)-AB (for other acidic mucopolysaccharide) double staining method.…”
Section: Acidophilus Jcm1034mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been reported that lectin-like activity of L. acidophilus group LAB was specific for strains. 27 ) To confirm this speculation, efforts will be directed to examine adhesion of L. acidophilus group LAB to epithelial cells of intestine with many bacterial strains.…”
Section: Discussionmentioning
confidence: 99%